Ideologi Tokoh Utama dalam Novel Ranah 3 Warna Karya A. Fuadi - Delfita, Yulia; Asri, Yasnur; Nurizzati, Nurizzati (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2013)
The purpose of this study was to describe the ideology of the main character in the novel Ranah 3 Warna works Ahmad Fuadi, which includes a reflection of ideology, familiis, sosialis, idealistic, religious, optimistic and sensitifis were illustrated from the behavior of figures. Type of research is a qualitative study using descriptive methods.The data in this study are sentences that describe the ideology of the main figures. Sources of data in this study is novel Ranah 3 Warna works Ahmad Fuadi.The findings of study are: (1) Aif Fikri as the main character, (2) the role ideology familiis, sosialis, idealistic, religious, optimistic, and sensitifis.